African Memory and Covert Attachments: Black Vernacular in Toni Morrison’s Beloved (SCHOLARS: Journal of Arts & Humanities, 2026)
This article explores black vernacular, which is part and parcel of the black community, rooted in African expressive culture, in Toni Morrison's Beloved. Black vernacular consists of rituals, blues, spirituals, secular songs and rhymes, jazz, prayers, sermons, and stories of various kinds. These vernacular genres are allied with the everyday life of the black community in the form of practices and performances, and manifest black life in the New World. These genres have played dual role in black community by simultaneously giving life to African heritage and sharing their pains and the moments of pleasure in the New World. Black people are communal in nature, and their togetherness reveals their pain and pleasure in communal activities, be it a birthday celebration or mourning rituals. The character, Baby Suggs, performs healing ritual in order to relieve her people from the worries of slavery. While exploring black vernacular with a special focus on their socio-cultural values in the New World in Morrison's Beloved, the researcher uses insights of black aesthetic as defined by Hoyt W. Fuller that fosters black life-world in artistic expressions. This article concentrates on how Morrison sustains black vernacular in Beloved and maintains African heritage in the New World. And this work urges further researchers in exploring native expressive cultures in literary texts.